Veluticeps fasciculata sp. nov. (Gloeophyllaceae, Basidiomycota), a close relative to V. berkeleyi - Yang, Jiao; Nakasone, Karen K.; He, Shuang-Hui (Phytotaxa, 2016)
A new brown-rot fungal species, Veluticeps fasciculata, is described from southern China. It is characterized by perennial effused basidiocarps with smooth or tuberculose hymenophore, nodose-septate generative hyphae, fasciculate cystidia (as hyphal pegs in hymenophore) and relatively small basidiospores. It occurs on wood of Cunninghamia and Cryptomeria. Although similar to Veluticeps berkeleyi, morphological and molecular (ITS rDNA sequences) data show that V. fasciculata is a distinct species. Complete description and illustrations are provided for the V. fasciculata. In addition, V. fimbriata is reported from China for the first time.